2017
DOI: 10.22246/jikm.2017.38.5.842
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Five Patients with Dyspepsia Improved after Korean Medicine Treatment, Including GeonChil Pharmacopuncture

Abstract: Obejective : Functional dyspepsia is a prevalent disease. It impedes subjective quality of life. The purpose of this research is to examine the equivalent effect of herb drug medicine treatment(H-D)and Over the Counter(OTC) for functional dyspepsia. Method :In this controlled study, we compared herb drug medicine(H-D) with Over the Counter(OTC) of functional dyspepsia. 30 volunteers who satisfied the requirements were enrolled in study. Severity of dyspepsia was measured by Nepean Dyspepsia Index(NDI-K) before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In a safety study of NPP, no toxicity was detected in the single intramuscular administration toxicity test [12] and micronucleus test [13]. Furthermore, no special adverse reactions were indicated in a case report of plantar fasciitis [11]. Nevertheless, further research is needed to confirm the clinical safety of these ingredients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a safety study of NPP, no toxicity was detected in the single intramuscular administration toxicity test [12] and micronucleus test [13]. Furthermore, no special adverse reactions were indicated in a case report of plantar fasciitis [11]. Nevertheless, further research is needed to confirm the clinical safety of these ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…No-pain (Mutong) pharmacopuncture (NPP) is a pharmawww.journal-jop.org copuncture solution that has been clinically used since 2022 to relieve musculoskeletal pain. To date, there have been few studies on NPP, including one case report [11] and two toxicity assessments [12,13]. The evaluation of genotoxicity is crucial in herbal medicines and traditional medicine practices as they have the potential to cause harmful mutations and damage genetic material, increasing the risk of diseases, such as malignant tumors [14].…”
Section: Introductionmentioning
confidence: 99%
“…The Jakyak-Gamcho decoction (PR and GR) is effective in relaxing gastrointestinal smooth and skeletal muscles and in relieving muscle spasms [17,18]. However, to the best of our knowledge, the efficacy or toxicity of NPP extract has not been previously evaluated, with the exception of one study that conducted a single-dose toxicity assessment [8], and a clinical report of efficacy in a case of plantar fasciitis [9]. Genotoxicity refers to the property of a substance to cause damage to cellular DNA or chromosomes [19].…”
Section: Discussionmentioning
confidence: 99%
“…It is made with qi formula (water type) to reduce pain during acupuncture and promote absorption [ 8 ]. However, while NPP continues to be used clinically, to the best of our knowledge, no studies have reported its efficacy and safety, other than a case report of one case of plantar fasciitis [ 9 ] and a single-dose muscle toxicity study [ 8 ].…”
Section: Introductionmentioning
confidence: 99%